Facile one-pot multicomponent synthesis and molecular docking studies of steroidal oxazole/thiazole derivatives with effective antimicrobial, antibiofilm and hemolytic properties - Ansari, Anam; Ali, Abad; Asif, Mohd; Rauf, Mohd Ahmar; Owais, Mohammad; Shamsuzzaman (Steroids, 2018)
A series of steroidal oxazole and thiazole derivatives have been synthesized employing thiosemicarbazide/semicarbazide hydrochloride and ethyl 2-chloroacetoacetate with a simple and facile one-pot multicomponent reaction pathway. The antimicrobial activity of newly synthesized compounds were evaluated against four bacterial strains namely Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive bacteria (Staphylococcus aureus and Listeria monocytogenes) in addition to pathogenic fungi (Candida albicans and Cryptococcus neofonnans). Bioactivity assay manifested that most of the compounds exhibited good antimicrobial activity. To provide additional insight into antimicrobial activity, the compounds were also tested for their antibiofilm activity against S. aureus biofilm. Moreover, molecular docking study shows binding of compounds with amino acid residues of DNA gyrase and glucosamine-6-phosphate synthase (promising antimicrobial target) through hydrogen bonding interactions. Hemolytic activity have been also investigated to ascertain the effect of compounds over RBC lysis and results indicate good prospects for biocompatibility. The expedient synthesis of steroidal heterocycles, effective antibacterial and antifungal behavior against various clinically relevant human pathogens, promising biocompatibility offer opportunities for further modification and potential applications as therapeutic agents.